Direct covalent grafting of an organic radical core on gold and silver. Issue 33 (5th April 2017) - Ajayakumar, M. R.; Alcón, I.; Bromley, S. T.; Veciana, J.; Rovira, C.; Mas-Torrent, M.
Abstract : A newly designed radical–anchor (R–A) molecule was synthesized and covalently grafted on Ag and Au surface at one atom distance preserving the molecular spin. Abstract : The functionalisation of surfaces with organic radicals, such as perchlorotriphenylmethyl (PTM) radicals or tris(2, 4, 6-trichloro-phenyl)methyl (TTM) radicals, is appealing for the development of molecular spintronic devices. Conventionally, organic radicals are chemisorbed to metal substrates by using long alkyl or aromatic spacers resulting in a weak spin–electron coupling between the radical and the substrate. To circumvent this problem, here we have employed a new design strategy for the fabrication of radical self-assembled monolayers (r-SAMs). This newly designed radical–anchor (R–A) molecule, a TTM based radical disulfide (1 ), can be easily synthesized and it was here characterized by electron spin resonance (ESR), cyclic voltammetry (CV) and superconducting quantum interference device magnetometry (SQUID). We have succeeded in fabricating TTM based r-SAMs by using thiolate bonds (Au–S and Ag–S) where the TTM cores are only one-atom distance from the metal surface for the first time. The resultant robust1 /Au and1 /Ag r-SAMs were well characterized, and the electrochemical and the magnetic properties were unambiguously confirmed, proving the persistence of the molecular spin.